Biochemical and Histological Parameters in Labeo rohita Inhabiting Aquatic Ecosystems of Ludhiana and Muktsar Districts of Punjab: Labeo rohita parameters in aquatic ecosystem - Kaur, Navdeep; Rapneet Kaur (Journal of Soil Salinity and Water Quality, 2023)
Labeo rohita were collected from  Farmer’s fish pond as well as village pond of Muktsar  and Farmer’s fish pond of Ludhiana  during 2019-20 in four seasons (summer, monsoon, post monsoon, winter). The protein content in liver, gills, kidneys and muscles of fish was significantly high in Farmer’s fish pond of Ludhiana as compared to village pond and Farmer’s fish pond of Muktsar during all and most of the seasons respectively. The protein content in different organs was observed to be significantly high in Farmer’s fish pond as compared to village pond of Mukstar during most of seasons. The lipid content in liver and other  organs (gills, kidneys and muscles) was significantly high in Farmer’s fish  pond of Ludhiana as compared to both Farmer’s Fish pond and village pond of Muktsar during post monsoon + winter and all seasons respectively. The lipid content in liver as well as gills and kidneys as well as muscles was observed to be significantly high in Farmer’s fish pond as compared to village pond of Mukstar during all and most of seasons respectively. The activity of AST and ALT was significantly high in liver and kidneys of both Farmer’s fish pond and village pond of Muktsar as compared to Farmer’s fish pond of Ludhiana during most of seasons. Severe histopathological lesions and alterations were observed in different organs of fish from Muktsar as compared to that of Ludhiana during most of seasons. Thus fish inhabiting ponds can be used as bioindicators for monitoring the quality of aquatic ecosystems.